G93(P) DO AS I SAY, NOT AS I DO? Differences between perceived and actual practice in the follow up of microscopic haematuria/proteinuria in febrile children seen in the children's emergency department. (27th April 2015) - Hastings, RA; Lunn, AJ; Surridge, J
Abstract : Aims: To examine the follow up of children with microscopic haematuria/proteinuria in the children's emergency department (CED) and to see if it differs from the perceived practice of CED doctors. Methods: An audit of children with a diagnosis of 'viral URTI' or 'viral illness' during one month in a busy (>30, 000 attendances/year) CED was performed. The follow up of those children with a recorded positive urine dipstick was examined. A survey of responses to scenarios of children with an incidental finding of microscopic haematuria/proteinuria (with no overt signs of renal disease) was used. The survey was sent to SHO grade doctors and registrars and asked for their current practice in arranging follow up of children with positive urine dipstick results. Results: 174 children were audited with 24 of them having a documented positive urine dipstick result. Seventeen children had a single positive (either haematuria/proteinuria), none had follow up. Seven children had at least 2+ of either proteinuria or haematuria and only one of these had any form of follow up arranged (14%). Online survey of SHO doctors (8) and registrars (12) showed that for a child with a 1+ positive urine dip only 5 doctors (25%) would arrange follow up. However 17 doctors (85%) said they routinely offer follow up to children with at least 2+ on urine dip (either haematuria or proteinuria). Conclusions: Approximately 2/3 of microscopic haematuria/proteinuria in children without specific renal symptoms resolves. Ensuring resolution is important since up to 50% of children in whom it persists have renal disease. 1 In our CED, only 14% of children with at least 2+ positive urine dipstick had follow up arranged. On survey, 85% of doctors working in CED stated that their current practice is to offer follow up to these same children. In regards to the management of haematuria/proteinuria, doctors' perceived practice in a busy CED setting differs markedly from their actual practice. Reference: Geary DF, Schaefer F. Comprehensive Pediatric Nephrology. Philadelphia: Mosby; 2008